Model Pengembangan Agroindustri Di Desa Gondangan Kecamatan Jogonalan Klaten - Didik Indarwanta; Ida Susi Dewanti; Asih Marini Wulandari (Jurnal Paradigma, 2015)
This study has the objective to create a model for the development of agro-industry Gondangan considering it has potency to be developed as a regional agro-industries. Gondangan village has many of home industries in the eld of snacks made from agricultural products. During the domestic industry is capable of providing welfare for the culprit. The development of agro-industry area is expected to provide greater added value for agricultural products, as well as increasing incomes. The method used is the Research and Development. This method is used to produce a particular product, and test the effectiveness of a particular product. The results showed that there were three main components in the agro-industry models consist of the main actors, supporting institutions, and related industries. Respondent of this study are home-industries owner as the main actor. The result show that home-industries owner business need assistance because, they do not have the characteristics of attitudes needed to develop a greater business. Ability and knowledge in the business also need to be developed through partnership program. Supporting institutions also need to be strengthened and involved in the partnership. Institutional support in this case is local government and cooperative. The related industry is a supplier of raw materials and distribution channels, agents and distributors, should be involved in the partnership program to ensure smooth supply to produsen. The three component of agro-industries should run well so that the model can be implemented well too.